Realizing Restorative Justice: Strengthening Job Training as a Criminal Sanction for Children in Conflict with the Law in Indonesia - Setyawan, Petrus Kanisius Iwan; Lisdiyono, Edy; ., Krismiyarsi (South Eastern European Journal of Public Health, 2024)
Job training as a criminal sanction for children in conflict with the law is a restorative justice approach that aims to rehabilitate and empower children while ensuring they take responsibility for their actions. However, its implementation in Indonesia is hindered by various challenges, such as the need for more specific policies, limited training infrastructure, and community stigma towards juveniles serving sentences. This research is focused on analyzing the policy strengthening and strategies needed to ensure the effectiveness of job training as a criminal sanction. The research methodology involves an empirical juridical method with a descriptive-analytical approach. Data is gathered from a literature review that includes legislation, policy documents, and related research findings, supplemented by the results of field research sourced from primary data. The analysis is centered on identifying the main obstacles in implementing job training and exploring solutions based on the principles of restorative justice. The results highlight the need for a more specific and comprehensive policy, the development of child-friendly infrastructure, and the improvement of human resource competencies to strengthen job training as a criminal sanction. It also underscores the importance of collaboration in successfully implementing job training, as this can significantly benefit children and society.